Mental health treatment preferences and challenges of living with multimorbidity from the veteran perspective - DiNapoli, Elizabeth A. (Int J Geriatr Psychiatry, 2016)
OBJECTIVE: To explore middle-aged and older veterans’ current disease-management practices, mental health treatment preferences, and challenges of living with multiple chronic health conditions (i.e., multimorbidity). METHODS: Semi-structured qualitative interviews and self-report measures were collected from 28 middle-aged and older (50 years of age or older) veterans with multimorbidity. RESULTS: Our sample of veterans with multimorbidity was, on average, mildly depressed and anxious with elevated stress and disability. Veterans acknowledged the interaction of physical and emotional symptoms, which caused greater difficulty with health care management and daily functioning. Veterans had many concerns regarding their physical and emotional health conditions, such as continued disease progression and the addition of other emotional and physical health complications. Veterans also identified specific self-care approaches for disease management (e.g., medication, healthy lifestyle practices, and psychological stress management techniques), as well as barriers to engaging in care (e.g., money, transportation, and stigma). Participants preferred a combination of medication, psychotherapy, and healthy lifestyle practices for mental health treatment. The majority of participants (88.5%) agreed that these mental health treatments would be beneficial to integrate into disease management for older veterans with multimorbidity. Lastly, veterans provided an array of recommendations for improving Veteran’s Administration services and reducing mental health stigma. CONCLUSIONS: These findings provide support for patient-centered approaches and integrated mental and physical health self-management in the Veteran’s Administration for middle-aged and older veterans with multiple chronic conditions.